Development and Validation of Scam Victimisation Risk Inventory (Svr-I) among Malaysian Population - Wan Shahrazad, Wan Sulaiman; Fatin Adha, Murad; Geshina Ayu, Mat Saat; Rozainee, Khairudin; Daniella Maryam, Mohamed Mokhtar; Saralah, Mariamdaran; Azianura Hani, Shaari; Mohammad Rahim, Kamaluddin (Allied Business Academies, 2022)
An increasing number of people have fallen victim to scam resulting in loss of money and psychological trauma. This in turn affects the financial sustainability of the person. A number of studies have shown that the tendency to become victims of scams is related to lack of knowledge and awareness of cyber security as well as psychological predispositions. Therefore, this study aims to identify what are the risks involved among scam victims in Malaysia and hence, develop a Scam Victimisation Risk Inventory (SVR-I). This study was conducted using a cross-sectional survey in a two-phase study. Phase 1 was the pilot study and Phase II was the validation of the scale study. A total of 150 respondents participated in Phase I and another 150 respondents were involved in Phase II. The data were analysed using an Exploratory Factor Analysis (EFA) for Phase I and Confirmatory Factor Analysis (CFA) in Phase II. Results from EFA extracted three factors with satisfactory Eigen values and factor loadings. Further analyses with CFA validated the three-factor structure of the Scam Victimisation Risk Inventory (SVR-I). This study implies the importance of identifying dimensions of hasty-urgency, trustful of inaccurate information and risk-seeking as the risks for commercial scam victims. SVR-I is concluded as a valid and reliable measure to assess scam victimisation risk.